Late Glacial-Holocene ecostratigraphy of the south-eastern Aegean Sea, based on plankton and pollen assemblages - Triantaphyllou, M.V.; Antonarakou, A.; Kouli, K.; Dimiza, M.; Kontakiotis, G.; Papanikolaou, M.D.; Ziveri, P.; Mortyn, P.G.; Lianou, V.; Lykousis, V.; Dermitzakis, M.D. (Geo-Marine Letters, 2009)
Quantitative analyses of coccolithophores, planktonic foraminifers, dinoflagellate cysts and pollen assemblages were carried out on shallow (NS-14) and deeper (NS-40) sediment cores from the south-eastern Aegean Sea. Nine coccolithophore (ACE 1–9) and nine planktonic foraminifer (APFE 1–9) ecozones, correlated with dinoflagellate cyst evidence, have been defined for the last ~14.5 cal. ka. Additionally, eight pollen assemblage zones (PAZ 1–8) have been recognised and correlated with the plankton ecozones. Although generally consistent with existing schemes for the central and eastern Mediterranean, the established high resolution ecostratigraphy has led to an expanded palaeoecological reconstruction of the Late Glacial–Holocene archive in the south-eastern Aegean Sea, defining two warm and humid phases at 9.3–8.6 and 7.6–6.4 cal. ka B.P., associated with the deposition of the early Holocene sapropel S1, and a third one between 5.2 and 4.2 cal. ka B.P. The high sedimentation rates which characterise the study area enabled the detection of even minor and brief climatic events in the Aegean Sea during S1 deposition times.